THE INHIBITING FACTORS IN THE IMPLEMENTATION OF WOMEN AND CHILDREN PROTECTION UNIT’S ROLESS IN LAW ENFORCEMENT OF IMMORAL CRIMINAL ACT COMMITTED BY THE CLOSEST ADULTS TO MINORS IN THE JURISDICTION OF KEPAHIANG POLICE RESORT - Davinsi Josie Sidabutar; Lidia Br Karo; Herlambang Herlambang (Universitas Bengkulu, 2021)
The increase in violence committed by parents and the closest adults to children brings a new concept that must be understood together where violence against children is not only a trivial matter and the private sphere, but has become the state and the public problem. Based on the facts and data that showed the rampant violence against children that often occurs in the area of Kepahiang Regency, namely, violence committed by parents and the closest adults to children, it becomes necessary for the efforts to protect children to be maximized. The protection efforts must be carried out by the police, especially by the Women and Children Service Unit. The Women and Children Service Unit also has main tasks contained in Article 3 of KAPOLRI Regulation Number 10 of 2007 concerning the Organization and Work Procedures of the Women and Children Service Unit within the Indonesian National Police environment. This study was conducted to obtain an overview, to understand and to analyze the factors inhibiting the implementation of the roles of Women and Children Protection Unit in law enforcement of immorality criminal acts committed by the closest adult to minors in the jurisdiction of Kepahiang Police Resort. The method applied in this study was an empirical juridical approach with qualitative analysis. The result of the study stated that the inhibiting factors in the implementation of the roles of Women and Children Protection Unit in law enforcement of immoral criminal acts committed by the closest adults to minors in the jurisdiction of Kepahiang Police Resort arose from internal and external factors.